Four new cave-dwelling Platocoelotes species (Araneae: Amaurobiidae) from Guangxi and Guizhou, China - Liu, Jie; Li, Shuqiang (Zootaxa, 2008)
Four new species of the genus Platocoelotes, collected from caves in Guangxi and Guizhou of southwestern China, are diagnosed, described and illustrated: Platocoelotes ampulliformis sp. nov., Platocoelotes brevis sp. nov., Platocoelotes furcatus sp. nov., and Platocoelotes strombuliformis sp. nov.. The type specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences in Beijing (IZCAS).